2023
DOI: 10.1111/eci.14105
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise in kidney disease: A commonly undervalued treatment modality

Mehmet Kanbay,
Sidar Copur,
Abdullah B. Yildiz
et al.

Abstract: BackgroundPhysical inactivity has been identified as a risk factor for multiple disorders and a strong association exists between chronic kidney disease (CKD) and a sedentary lifestyle. Even though physical activity is crucial in the development and progression of disease, the general focus of the current medical practice is the pharmacological perspective of diseases with inadequate emphasis on lifestyle intervention.MethodsIn this narrative review we explain the pathophysiological mechanisms underlying the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 109 publications
(183 reference statements)
0
1
0
Order By: Relevance
“…As renal function declines, CKD patients experience a decrease in cardiopulmonary function and the onset of muscle atrophy [ 5 , 6 ], which significantly impacts prognosis and quality of life. Engaging in regular exercise can mitigate the limitations of medication, enhance physical function and muscle strength in individuals with CKD, reduce systemic inflammation, and slow the progression of renal impairment [ 7 , 8 ]. An observational study found that higher levels of physical activity were associated with a slower decline in glomerular filtration rate among CKD patients at Stages 3 and 4 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As renal function declines, CKD patients experience a decrease in cardiopulmonary function and the onset of muscle atrophy [ 5 , 6 ], which significantly impacts prognosis and quality of life. Engaging in regular exercise can mitigate the limitations of medication, enhance physical function and muscle strength in individuals with CKD, reduce systemic inflammation, and slow the progression of renal impairment [ 7 , 8 ]. An observational study found that higher levels of physical activity were associated with a slower decline in glomerular filtration rate among CKD patients at Stages 3 and 4 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Counselling and promotion of physical activity among CKD patients is an insufficiently addressed part of CKD management in clinical practice (Kirkman, Lemon-Edwards, & Edwards, 2014;Barcellos et al, 2015;Lightfoot et al, 2022;Kanbay et al, 2024). Regular and adequate physical activity improves nutritional status, and physiological, psychological, and social well-being, and prevents deterioration of muscle function and mass in CKD patients (Barcellos et al, 2015;.…”
Section: Implications For Practice and Policymentioning
confidence: 99%